2004
DOI: 10.1017/s0954579404044499
|View full text |Cite
|
Sign up to set email alerts
|

The course of maternal depressive symptoms and maternal sensitivity as predictors of attachment security at 36 months

Abstract: We examined the course of maternal depressive symptoms and children's attachment security at 36 months in a large sample of mother-child pairs from 10 sites across the country participating in the NICHD Study of Early Child Care~N ϭ 1077!. Maternal depressive symptoms predicted higher rates of insecure attachment. Women who reported intermittent symptoms across the first 36 months had preschoolers who were more likely to be classified as insecure C or D; women with chronic symptoms were more likely to have pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
2
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(196 citation statements)
references
References 42 publications
5
179
2
10
Order By: Relevance
“…28,29 Specifically, mothers who are more sensitive and responsive to their children are more likely to have children with secure attachment. 28 The symptoms of maternal depression can lead to unresponsive, inconsistent, unavailable, or rejecting care by the mother toward the child (i.e., decreased sensitivity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Specifically, mothers who are more sensitive and responsive to their children are more likely to have children with secure attachment. 28 The symptoms of maternal depression can lead to unresponsive, inconsistent, unavailable, or rejecting care by the mother toward the child (i.e., decreased sensitivity).…”
Section: Introductionmentioning
confidence: 99%
“…28 The symptoms of maternal depression can lead to unresponsive, inconsistent, unavailable, or rejecting care by the mother toward the child (i.e., decreased sensitivity). 29 Consequently, depressed mothers are more likely to be intrusive and harsh with their infants, 28,29 less likely to use safety precautions, such as car seats and child-proof latches on cabinets, 30,31 and less likely to engage in enriching parenting practices, such as reading, singing, and playing games with their child. 32 In addition, perinatal depression can significantly impact the couple's relationship.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to depression, in their meta-analysis of 46 studies Lovejoy, Graczyk, O'Hare, and Neuman (2000) found moderate effect sizes for the relation between maternal depression and maternal negative or disengaged behaviors and a small effect size for the relation between maternal depression and positive behaviors. More recent studies continue to confirm these findings (e.g., Campbell, Brownell, & Hungerford, 2004;Cummings, Keller, & Davies, 2005) With respect to anxiety, Whaley, Pinto, and Sigman (1999) found that anxious mothers compared to non-anxious controls scored higher on measures of criticism and catastrophizing and lower on measures of enthusiasm, warmth, and granting of autonomy. Similarly, Woodruff-Borden, Morrow, Bourland and Cambron (2002) found that compared to control parents, more anxious parents were more withdrawn and disengaged and exhibited fewer productive behaviors like agreeing or praising their children.…”
Section: Psychological Distressmentioning
confidence: 86%
“…Os bebês se aconchegam pouco, têm pouca reciprocidade com suas mães e expressão emocional diminuída, são irritados e choram mais, têm mais problemas de alimentação e sono e menor desenvolvimento motor 52 . Estudos de follow-up com crianças de mães com DPP demonstram que essas crianças têm menos segurança afetiva 53 , apresentam maior incidência de distraibilidade, alterações de comportamento, atraso no desenvolvimento cognitivo e transtornos afetivos [54][55][56][57] .…”
Section: Tabela 1 Prevalência De Depressão Pós-parto No Brasilunclassified